THE RELATIONSHIP OF CREDIT CHARACTERISTICS AND COAL PRICE WITH REPAYMENT CAPACITY: CASE STUDY OF A HEAVY EQUIPMENT LEASING COMPANY - Endru Subekti, Hanifa
In 2015 and 2016, heavy-equipment leasing company have felt either stagnation or reduction in their business. Many company forced to sized-down their business because of the condition. Deputy of OJK also said that in 2015, heavy equipment leasing company has the highest level of non-performing financing (NPF) compared to other leasing with 4.34%. This research has an aim to find the determinants of NPF in a heavy-equipment leasing company.